Vagal blood volume receptors compensate for haemorrhage and posture change - Zhikai Liu; Shan Lu; Isabela A. Haskell; Michael S. Schappe; Maša Josipović; Soohong Min; AbdulRasheed A. Alabi; Jingyi Chi; Minseon Kim; Stephen D. Liberles (Nature, 2026)
Abstract Cranial nerves densely innervate the heart and vasculature, with sensory neurons reporting on blood pressure, respiratory gases and tissue damage 1 . The roles of arterial baroreceptors in systemic physiology are well appreciated 2 , but the functions of vagal cardiac mechanoreceptors have been more difficult to parse, in part due to the closed-loop structure of the cardiovascular system. Here we use genetic tools in mice to identify a small group of neurons that are acutely sensitive to circulating blood volume and initiate a reflex that compensates for decreased filling of the heart in an upright posture and haemorrhage. Vagal PIEZO2 neurons form characteristic end-net endings in the heart, lower blood pressure in response to optogenetic stimulation and display blood-volume-dependent responses with every heartbeat that are time-locked to atrial and ventricular systole. Knockout of Piezo2 and/or ablation of PIEZO2 neurons in vagal ganglia eliminates this heartbeat-coupled nerve activity, causes orthostatic hypotension and compromises cardiovascular stability during trauma-induced blood loss. Together, these findings demonstrate that vagal mechanoreceptors monitor the cardiac cycle and initiate a blood-volume-dependent reflex that defends the constancy of circulation.